2005
DOI: 10.1002/jnr.20670
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of γ‐aminobutyric acid‐A receptor subunits in rat dorsal and ventral hippocampus

Abstract: Recent data demonstrate weaker gamma-aminobutyric acid (GABA)-ergic inhibition in ventral (VH) compared with dorsal (DH) hippocampus. Therefore, we examined possible differences regarding the GABAA receptors between VH and DH as follows: 1) the expression of the GABAA receptor subunits (alpha1/2/4/5, beta1/2/3, gamma2, delta) mRNA and protein and 2) the quantitative distribution and kinetic parameters of [3H] muscimol (GABAA receptor agonist) binding. VH compared with DH showed: 1) lower levels for alpha1, bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0
23

Year Published

2006
2006
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 86 publications
4
35
0
23
Order By: Relevance
“…The differential density of Cx36-puncta in the SL of the ventral vs. dorsal hippocampus implies differential expression of Cx36 in granule cell projecting to these regions, and adds to other differences that have been described in dorsal vs. ventral hippocampus (Papatheodoropoulos and Kostopoulos, 2000, 2002a,b; Papatheodoropoulos et al, 2002, 2005; Sotiriou et al, 2005). Pertinent in this regard are implications of abnormal neuronal gap junctional coupling in initiation, maintenance, and spread of epileptic activity and in hypersynchronous activity associated with seizures (Perez et al, 2000; Pike et al, 2000; Rouach et al, 2002; Traub et al, 2001).…”
Section: Discussionmentioning
confidence: 67%
“…The differential density of Cx36-puncta in the SL of the ventral vs. dorsal hippocampus implies differential expression of Cx36 in granule cell projecting to these regions, and adds to other differences that have been described in dorsal vs. ventral hippocampus (Papatheodoropoulos and Kostopoulos, 2000, 2002a,b; Papatheodoropoulos et al, 2002, 2005; Sotiriou et al, 2005). Pertinent in this regard are implications of abnormal neuronal gap junctional coupling in initiation, maintenance, and spread of epileptic activity and in hypersynchronous activity associated with seizures (Perez et al, 2000; Pike et al, 2000; Rouach et al, 2002; Traub et al, 2001).…”
Section: Discussionmentioning
confidence: 67%
“…This underlines that the magnitude of potentiation does not depend solely on the sheer number of interneurons but rather on the overall excitatory/inhibitory balance. While detailed investigations of dorsovental differences regarding inhibitory processes in the DG are missing, studies in the CA1 region suggest marked differences in GABA A -receptor mediated recurrent inhibition 33 , which are best explained by dorsoventral differential expression of particular subunits, leading to contrasting properties of the synaptic pentameric GABA A -receptor protein complexes 34 . On the other hand, distinct proportions of certain subunits (such as α4, β3 and δ) in extrasynaptic GABA A -receptors could result in dorsoventral differences in tonic inhibition 34, 35 , but our measurements did not provide evidence for this.…”
Section: Discussionmentioning
confidence: 99%
“…In the adult HPC, a5GABA A R are located extrasynaptically, primarily in the dendritic fields of CA1, CA3, dentate gyrus, and subiculum (Sur et al, 1999). In addition, a5GABA A R expression and binding is greater in the ventral HPC, mainly stratum lacunosum-moleculare, in comparison with the dorsal HPC (Sarantis et al, 2008;Sotiriou et al, 2005), suggesting that targeted agonism of this GABA subunit would alter ventral HPC activity selectively. It has been shown that extrasynaptic GABA A receptors mediate tonic inhibitory conductances, at both pyramidal and dentate granule cells (Bai et al, 2001;Nusser and Mody, 2002).…”
Section: Discussionmentioning
confidence: 99%